Membangun Sistem Informasi Ujian Online Menggunakan Metode Fisher Yates Shuffle di Smp Islam At-Taqwa - Wahyudi Wahyudi; Ahmad Fikri Zulfikar (Institut Sains dan Teknologi Nasional, 2023)
Abstract From the development of technology that exists today has influenced many aspects, one of which is the educational aspect. In the aspect of education, technology has influenced the use of media that can facilitate the process and administration of learning so as to increase effectiveness and efficiency. Although from the current technological developments, unfortunately SMP ISLAM AT-TAQWA still conducts exams offline so it requires paper and a place to carry out exams, if the exam is only done offline there is cheating when carrying out the exam, especially during the current pandemic at SMP ISLAM AT-TAQWA still uses google forms to carry out exams, so that the implementation of exams is less efficient to do, There is no application to support online exams. The solution to overcome this problem is to make an online exam application with questions on the online exam application to be random using the Fisher yates Suflle method to minimize cheating when carrying out the exam. With this online exam application, it makes it easier for students to carry out exams so that students can carry out exams anywhere and anytime, and can make it easier for teachers to make exam questions and also save paper when carrying out exams. The results of this study resulted in an online exam application that has been tested, so that users in this application can be helped as the results of observations made by the author in conducting this study.